Entrepreneurship Management in Enhancing the Self-Reliance of Islamic Boarding Schools - Chairul Anwar; Muhammad Ahsan Zulfiqar (Al-Abshar: Journal of Islamic Education Management, 2026)
This study is motivated by the suboptimal economic independence of Islamic boarding schools (pesantren) due to their dependence on external funding sources, highlighting the need for management strategies capable of strengthening institutional sustainability. This research aims to analyze the implementation of entrepreneurship management in enhancing economic independence at Sumber Baru Al-Falah Islamic Boarding School. The study employed a qualitative approach with a case study design. Data were collected through observation, in-depth interviews, and documentation involving the pesantren leader, business unit managers, and students (santri). Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing, while data validity was ensured through source and technique triangulation. The findings reveal that entrepreneurship management is implemented through the functions of planning, organizing, actuating, and controlling in managing the pesantren's productive business units. This implementation contributes to strengthening the economic independence of the pesantren through the optimization of internal resources, business innovation development, and the involvement of students in economically productive activities. The success of the implementation is supported by visionary leadership, active participation of the pesantren community, and the utilization of local economic potential. However, several challenges remain, including limited capital, managerial competence, and market dynamics. The study concludes that entrepreneurship management serves as an important strategy for developing a sustainable and adaptive model of pesantren independence. Theoretically, this research enriches the discourse on Islamic educational management, particularly regarding the integration of entrepreneurial principles into the management of Islamic boarding schools. Practically, it offers an entrepreneurship management implementation model that can serve as a reference for pesantren in developing productive business units to strengthen economic independence and institutional sustainability.